“In retrospect, I recognize it as a significant turning point”: A graduate student-centered assessment of a Preparing Future Faculty program - Aybike Tezel; Charmian Lam; David Daleke; Helen Hathorn; jay Howard; Julie Eyink; Julie Saam; Katherine Kearns; Leslie Drane; Matthew G Standard; Melissa O'Neill (To Improve the Academy)
Preparing Future Faculty (PFF) programs provide pedagogical training and experiences to promote graduate student professional development. We conducted a study of PFF Fellows’ experiences about their year of teaching between 2005 and 2020 and subsequent career trajectory. This is particularly interesting as Fellows have a variety of experiences while teaching in-person at one of seven collaborating host institutions before graduating and pursuing a career. Using a mixed methods survey (n = 54), we provide a student-centered assessment of program goals across 15 annual cohorts from a home institution classified as large, Midwestern, and public. Descriptive and thematic analysis of responses revealed five themes suggesting that PFF experiences have positive outcomes for graduate students’ academic career development. As our methodological goal was to center graduate student voices, we have provided several narratives that illustrate the diversity of experiences across the years. We discuss the implications of these findings as important considerations for the creation of similar programs designed to support graduate student development as future faculty.